Discharge Plan for Parents having Children Suffering from Head Trauma - Walaa Abd Allah El-Tayar; Eman Amin Mohammed; Salma El Sayed Hassan; Hyam Refaat Tantawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Effective discharge planning is a vital component to maintain care continuity for head traumapediatric patient. Despite this, there is a critical gap in the process and quality of discharge planning in Egypt.Aim of this studywas to assess the effect of discharge plan on parents having children suffering from headtrauma.Design: A quasi- experimental design was used.Settings: This study was conducted in Emergency Department, Pediatric Intensive Care Unit (PICU) andNeurological Department at children Hospital affiliated to Ain Shams University and El-Menshawy Hospitalin Tanta affiliated to Ministry of Health.Subject: A convenient sample consist of 40 parents accompanied their children suffering from head traumawho attended in the previously mentioned settings.Tools: 1)- Pre-designed questionnaire sheet which included two parts: part I: concerned with characteristicsof studied parents and characteristics of the studied children,Part II: knowledge of the parents regardingcaring of their children suffering from head trauma, 2)- Observational check list and 3)- Child MedicalRecord.Results: All of studied parents reported that no one gave them any information about head trauma. There wasa marked improvement in parents’ knowledge and reported practices post implementation of discharge plan.There were strong positive correlations between studied parents’ total knowledge and their total reportedpractices related to care of children after head trauma pre/post discharge plan.There was highly statisticalsignificance difference between parents’ total knowledge regarding care of head trauma in children andtheir level of education post implementation of discharge plan. There was statistical significance differencebetween parents’ total reported practices regarding care of head trauma in children and their level of educationpost implementation of discharge plan.Conclusion: All of research hypothesis were accepted and implementation of discharge plan led to significantimprovements in parents’ knowledge and reported practices regarding care of their children suffering fromhead trauma. Recommendations: Discharge plan for all parents having children suffering from head trauma must beginwith parents at their first day of admission.